A stochastic thunderstorm model for dynamic response assessment - School of Civil and Environmental Engineering (2008)
Thunderstorm winds have been known to be highly non-stationary as compared to other large scale winds like monsoons. The highly localized nature of these winds generates ferocious winds at low to mid-height, deviating from the boundary layer wind profile that most building codes recognized. The thunderstorm downdraught rushes down vertically and spreads out radially like a wall-jet. Highest wind speeds are registered at locations which are nearest to the storm cell centre.